Properties of particleboard from oil palm trunk (Elaeis guineensis) / Noor Fariza Zafri and Siti Nur Fatimah Ahmad - Zafri, Noor Fariza; Ahmad, Siti Nur Fatimah (2008)
Oil palm trunk (Elaeis guineensis jacq) has now becoming the most important raw materials in wood industries in Malaysia. However its important for production of reconstituted wood based products and furniture can be future enhance through research and development. This study examined the physical and mechanical properties of particleboard made from 2mm oil palm trunk particle in various densities, percentage of resin and wax addition. The result show that the strength properties of particleboard namely the Modulus Of Rupture (MOR), Modulus Of Elasticity (MOE) and internal Bonding (IB) will affect when increasing and decreasing of additives. From this study, the good particleboard is with high density, resin content and without wax addition. In this project, the good variation for oil palm trunk particleboard is the board with 700 kg/m3, 12 % resin content and without wax addition.